Modern MultiPort Converter Technologies: A Systematic Review - Levon Gevorkov; José Luis Domínguez-García; Lluis Trilla Romero; Àlber Filbà Martínez (Applied Sciences, 2023)
The integration of renewable energy sources (RES) as distributed generation units to the power grid has been accelerated by the rising demand for energy and the growing concern over the environmental effects of conventional sources. At the same time, modern electric vehicles (EV) are demonstrating a promising ability to decrease the consumption of fossil fuels. The issues related to a combination of various renewable energy sources to fulfil the load requirements can be solved by the application of multi-input–output architecture that is properly designed. In order to increase the driving range of EVs, several energy sources, including ultracapacitors and fuel cells, should be connected and operate in combination with a battery storage system. To manage these energy sources with various voltage-current characteristics, the same concept can be applied. The current trends in the field of multiport DC-DC converters are identified and examined in this research. This paper proposes a review and analysis of the most significant aspects of multiport converters, such as types based on various characteristics, their topologies, the benefits and drawbacks, and areas of application. A thorough investigation of multiport converters’ design guidelines and selection process for specific applications is presented. Based on their properties, multiport converters are categorized in this review. In comparison with other available review publications, this paper is more concise and mainly focused on the most general and important aspects of multiport technologies. Based on the provided information, the reader can discern modern trends and directions of the multiport converter development.